Fully automated analysis of chemically induced γH2AX foci in human peripheral blood mononuclear cells by indirect immunofluorescence. Issue 11 (5th September 2013) - Willitzki, Annika; Lorenz, Sebastian; Hiemann, Rico; Guttek, Karina; Goihl, Alexander; Hartig, Roland; Conrad, Karsten; Feist, Eugen; Sack, Ulrich; Schierack, Peter; Heiserich, Lisa; Eberle, Caroline; et al.
Abstract Analysis of phosphorylated histone protein H2AX (γH2AX) foci is currently the most sensitive method to detect DNA double‐strand breaks (DSB). This protein modification has the potential to become an individual biomarker of cellular stress, especially in the diagnosis and monitoring of neoplastic diseases. To make γH2AX foci analysis available as a routine screening method, different software approaches for automated immunofluorescence pattern evaluation have recently been developed. In this study, we used novel pattern recognition algorithms on the AKLIDES® platform to automatically analyze immunofluorescence images of γH2AX foci and compared the results with visual assessments. Dose‐ and time‐dependent γH2AX foci formation was investigated in human peripheral blood mononuclear cells (PBMCs) treated with the chemotherapeutic drug etoposide (ETP). Moreover, the AKLIDES system was used to analyze the impact of different immunomodulatory reagents on γH2AX foci formation in PBMCs. Apart from γH2AX foci counting the use of novel pattern recognition algorithms allowed the measurement of their fluorescence intensity and size, as well as the analysis of overlapping γH2AX foci. The comparison of automated and manual foci quantification showed overall a good correlation. After ETP exposure, a clear dose‐dependent increase of γH2AX foci formation was evident using the AKLIDES as well as Western blot analysis. Kinetic experiments on PBMCs incubated with 5 μM ETP demonstrated a peak in γH2AX foci formation after 4 to 8 h, while a removal of ETP resulted in a strong reduction of γH2AX foci after 1 to 4 h. In summary, this study demonstrated that the AKLIDES system can be used as an efficient automatic screening tool for γH2AX foci analysis by providing new evaluation features and facilitating the identification of drugs which induce or modulate DNA damage. © 2013 International Society for Advancement of Cytometry